Gratitude as a systems-wide values-based approach to enhance sustainable consumption choices - Schutt, Vince (YU-WRITE: Journal of Graduate Student Research in Education, 2023)
What if the best approach to solve climate change were to emphasize an emotion felt by the majority of the population? Robin Wall Kimmerer’s Braiding Sweetgrass presents gratitude as a powerful emotion. This article is a deep theoretical exploration of gratitude, largely informed by Indigenous oral histories as presented by Kimmerer. The analysis shows gratitude as having the potential to serve as an emotional (rather than logical) catalyst for change in human consumption behaviours. Also explored is how gratitude can form a cyclical system interwoven with care, gifts, and reciprocity. Environmental activists have been seeking to enact change, largely through a wide-range of education-scoped efforts. Yet change doesn’t happen. This article argues that Indigenous wisdom on the practice and experience of gratitude offers a profoundly more satisfying approach to human relationships; both with nature and other humans. Ultimately gratitude, when more deeply experienced, seems capable of inspiring new programs of actions, education, and efforts to affect highly meaningful and engaging societal transformation towards greater ecological responsibility.